Re-elevation of d-dimer as a predictor of re-dissection and venous thromboembolism after Stanford type B acute aortic dissection - Jo, Yusuke; Anzai, Toshihisa; Ueno, Koji; Kaneko, Hidehiro; Kohno, Takashi; Sugano, Yasuo; Maekawa, Yuichiro; Yoshikawa, Tsutomu; Shimizu, Hideyuki; Yozu, Ryohei; Ogawa, Satoshi (Heart and Vessels, 2010)
d -dimer measurement is a useful complementary initial diagnostic marker in patients with acute aortic dissection (AAD). However, it has not been clarified whether serial measurements of d -dimer are useful during in-hospital management of Stanford type B AAD. We studied 30 patients who were admitted with diagnosis of Stanford type B AAD and treated conservatively. d -dimer was serially measured on admission and then every 5 days during hospitalization. Patients were divided into two groups according to the presence or absence of re-elevation of d -dimer during hospitalization, in which d -dimer transition were biphasic and latter peak >10.0 μg/ml. Re-elevation of d -dimer was observed in 17 patients. There were no differences in atherosclerotic risk factors, blood pressure on admission, d -dimer level on admission, extent of AAD, and false lumen patency. Patients with re-elevation of d -dimer showed higher incidence of re-dissection and/or venous thromboembolism (VTE). Peak d -dimer level in patients with re-dissection and/or VTE was significantly higher than that without these complications ( p = 0.005). In conclusion, serial measurements of d -dimer are useful for early detection of re-dissection or VTE in patients with Stanford type B AAD, which may contribute to the prevention of disastrous consequences such as pulmonary embolism and extension of AAD.